Market and Regulatory Coefficients for Determining the Rent for Public Land in Regions - Samsonov, Ruslan A.; Bocharov, Sergey N.; Mishchenko, Vitalii V.; Kobrin, Mikhail Yu. (Economy of Regions, 2021)
As opposed to international studies, Russian scientists apply multifactorial models with specific coefficients to determine the rent for public lands. This research analyses and summarises the existing theoretical and normative approaches to coefficient calculation covered by domestic literature. We examine two types of coefficients: permitted use of land (K) and categories of land users (K1). Based on the property valuation theory (income and comparative approaches), we demonstrated problems and disadvantages of the methods currently used to determine K and K1 coefficients. Then, using the economic contract theory, we identified market and non-market (hybrid and hierarchical) regulation mechanisms and distinguished K and K1 coefficients. Institutional differences of these indicators were theoretically substantiated. As a result, we developed economic algorithms for calculating market (K) and regulatory (K1) coefficients that take into account both types of permitted use of land (for K) and categories of land users (for K) by considering preferences and restrictions in the field. The elaborated methodology was tested by performing complex calculations, which allowed us to obtain the values of K and K1 coefficients for 18 local councils located in Pervomaysky District of Altai Krai for 112 types of permitted use of land. Proposed methodological recommendations can be applied for developing municipal programmes in Russia and abroad to increase the effectiveness and transparency of public land rent.